The role of socioeconomic and behavioral factors in HIV-related deaths - Dincer, Metin; Kose, Nezir; Unal, Emre (Springernature, 2024)
In today's increasingly interconnected globe, there continues to be a pressing need for thorough research that can shed light on the causes of HIV-related mortality and the primary factors at play in this epidemic. By using an annual dataset, this study analyzed the impact of behavioral risk factors, income, and human capital on HIV-related deaths (HIVD) across all countries and regions. The empirical findings of the panel regression demonstrate that drug use and unsafe sex have a statistically significant and positive effect on HIVD. On the other hand, mean years spent in school and gross national income per capita both have a statistically significant and negative influence on HIVD. The findings of the variance decomposition suggest that drug use should be confronted in wealthy nations to lower HIVD, but both human capital and economic development have a greater influence on the battle against HIVD in underdeveloped and developing countries. In addition, the findings of the panel Granger causality test demonstrate that factors other than unsafe sex can be used as leading indicators in the process of forecasting HIVD. According to these findings, economic variables, as well as behavioral risk factors in emerging nations, and in industrialized countries, should be taken into account when formulating strategies for preventing HIV/AIDS.
Keywords: Injection-Drug Users; Condom Use; Hiv/Aids Mortality; Risk Behaviors; Impact; Alcohol; Aids; Sex; Prevalence; Survival